The impact of firm-influenced vocational education on labor market and demographic outcomes - Adrian Mehic; Arian Mosaddegh (Research Institute of Industrial Economics (IFN), 2025)
This paper examines the impact of a Swedish policy allowing manufacturing firms to influence the curricula of local educational institutions. Our analysis shows that the program has contributed to a significant reduction in youth unemployment, as well as an increase in marriage rates and male fertility rates at the municipality level. We further show that these positive labor market outcomes are due to improved quality and relevance of vocational education, rather than an increase in the number of graduates. However, using data covering the universe of Swedish firms, we find that manufacturing firms in neighboring municipalities saw declines in productivity, suggesting some negative spillover effects of the program.
Keywords: E24; I26; J12; J24; 330; Youth unemployment; Vocational education; Fertility